Menulis, Komunikasi dan Humaniora - Tulasi, Dominikus (Bina Nusantara University, 2011)
This article is a potrait of constructing frame of mind in writing, communication and human being. Communication is a process of transforming idea to the other in which the idea can be formed through encoding process to be reformed and reconstructed in decoding process by receiver. The new order framework is the new paradigm of mind. Further more, writing is an action to pour idea to be sedimented and embeded in the form of documented written. Related to writing, communication means transfering message from sender to the other either verbal and or non-verbal process. On the other hand, humaniora is a realm of meaning within human spirit to be humanized and civilized by oneself through education. Educating human being is also a teaching and learning process toward oneself-personalization. The personalization is so called humanization process.